U-band multiwavelength Brillouin-Raman random fiber laser with single Brillouin frequency spacing - Abdulghani, Amer; Abdo, Salah; Al-Alimi, A.W.; Shee, Y.G.; Cholan, N.A.; Zainuddin, N.H.; Mahdi, M.A. (Elsevier Ltd, 2023)
A single Brillouin frequency interspacing (∼10 GHz) multiwavelength Brillouin-Raman random fiber laser with lasing operation in the U-band is demonstrated through nonlinear interactions of stimulated Raman scattering and stimulated Brillouin scattering as amplification mechanisms. Structurally, dispersion compensation fiber of 11.2 km length was employed as a highly nonlinear gain medium. For a single Brillouin frequency interspacing operation, a quasi-bidirectional double pass distributed Raman amplification was proposed by looping back the forward lasing spectrum together with the residual Raman signal into the laser cavity. The optimized Raman pump power was set to 1020 mW at 1550 nm; whereas Brillouin pump power and wavelength were optimized at 0 dBm and 1640 nm respectively. Under these conditions, 476 channels interspaced by 10 GHz and spectrally flattened within 3 dB peak power variation were generated over ∼40.8 nm spectral bandwidth from 1640.9 to 1681.7 nm, with 16.28 dB average optical signal-to-noise ratio, and −15.25 dBm average Stokes peak power. Meanwhile, total output power of 19.77 dBm was recorded at 20 % optical power conversion efficiency with 0.10 dB power fluctuation during 1 hour of continuous operation at ambient conditions. The proposed U-band Brillouin-Raman random fiber laser has potential applications in optical communication, optical sensing, and microwave photonics.